EFEKTITAS TERAPI MURROTAL AL-QUR’AN SURAH AR-RAHMAN TERHADAP PENURUNAN NYERI PADA PASIEN KANKER - Zainatun " Hasanah; Nurul " Huda; Siti " Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstrack   This study’s objectives are to determine Qur'an MURROTAL therapy effectiveness of Ar-Rahman Surah to decrease pain in breast cancer patients who is using  quasy experiment research design with the pretest-posttest research design with control group. Samples are 34 respondents who is divided into 17 experimental group and 17 control group is taken based on inclusion criteria using purposive sampling technique. Measuring instruments used in the group is the observation sheet in the form of pain intensity scale NRS (Numeric Rating Scale) with a scale of 1-10. The analysis used univariate and bivariate analysis with the Wilcoxon and Mann-Whitney test. The results indicate an average pain intensity in patients with breast cancer after given Qur'an MURROTAL therapy of Ar-Rahman Surah in the experimental group is 2.84 and in the control group that is not given Qur'an MURROTAL therapy of Ar-Rahman Surah is 4.86. The statistical results obtained p value (0.000) <α = 0.05, so it can be concluded that the Qur'an MURROTAL therapy of Ar-Rahman Surah is effective to pain intensity reduction in breast cancer patients. The research results recommends as a non-pharmacological interventions in the hospital Keyword:Breast cancer, murrotal Al-Qur’an surah Ar-Rahman, pain